Agricultural value chain interventions can improve women's incomes, assets holdings, productivity and savings - Malhotra, Suchi Kapoor; Masset, Edoardo (CGIAR System Organization, 2024)
Agricultural value chain interventions, such as market integration strategies, negotiating better prices and developing new and more pro table products are important mechanisms to increase farm incomes. While women play a critical role in agriculture, power dynamics and sociocultural norms often restrict their participation to parts of the agricultural value chain that have the least economic returns, such as agricultural labor, petty trading and subsistence farming. Evidence indicates value chain interventions are successful at improving women’s incomes, assets holdings, productivity and savings. However, this economic advancement is not enough to translate into noneconomic empowerment, such as altering gender roles and removing cultural barriers within families and communities.